PENGARUH PROFITABILITAS, LIKUIDITAS, EFISIENSI, NET INTEREST MARGIN DAN NON PERFORMING LOANTERHADAP CAPITAL ADEQUACY RATIO PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - Julindo Akhbal Fajar, 14.05.52.0042; Srimindart, Ceacilia (Students' Journal of Accounting and Banking, 2018)
ABSTACT This study aims toexamine the effect of company size, and leverage of going concern audit opinion. This research was conducted at the companies listed on the Stock Exchange in 2014-2016. The samples used were as many as 336 observations selected using purposive sampling method. Data collection was done by using the documentation obtained from BEI website and Pojok BEI-Unisbank Stikubank (Unisbank). The analysis technique used is logistic regession.The results of the analysis of this study indicate only leverage ratio is able to affects the going concern audit opinion of manufacturing company, while the company size is not able to influence the probability of going concern audit apinion. Keywords: Company Size, Leverage,Going concern Audit Opinion